Estrategias de comercialización para incrementar las ventas de productos orgánicos a través de la fundación Swissaid –Ecuador en la comunidad de Condorahua, perteneciente a la parroquia El Rosario del cantón Pelileo, período 2022 - Criollo Sánchez, Bélgica Isabel (2022)
The purpose of this research was to design marketing strategies as a tool to increase sales of organic products through the SWISSAID Foundation in the Condorahua Community, which was based on a description of the problem that allowed formulating, justifying and setting clear objectives study. Consecutively, a theoretical, conceptual and legal framework was presented that allowed the study of the proposed variables. Next, a methodology was established, the same one that had a quantitative and qualitative approach, of a descriptive type, the information was collected through the application of surveys to the Economically Active Population of the Community of Condorahua and the application of a survey both to the legal representative SWISSAID Foundation - Ecuador as well as the leader of the farmers in the sector, for further analysis. The results revealed that the producers do not have marketing strategies, therefore, the sales of organically grown products do not generate significant income due to the lack of marketing. The statistical method to be used to verify the hypothesis was the Chi Square Test present in the statistical program SPSS, the same one that allowed accepting and demonstrating the research hypothesis with a significance value of 0.000. Finally, the proposal for the implementation of marketing strategies is presented through the SWISSAID Foundation, which will provide all the necessary support to improve the standard of living of producers and consumers. Keywords: Strategy, Sales, Marketing, Organic Product.